Patient perspectives on priorities for emergency medicine research: The PERSPEX study - McLay, S.; McCutcheon, D.; Arendts, Glenn; Macdonald, S.; Fatovich, Daniel (Wiley-Blackwell Publishing Asia, 2018)
© 2017 Australasian College for Emergency Medicine and Australasian Society for Emergency Medicine Objectives: To determine the priorities for emergency medicine research of patients currently in an ED and to compare their priorities with those of ACEM researchers. Methods: A survey of current patients in the EDs of Royal Perth Hospital and Armadale Health Service. Patients gave their reason for presentation, suggested three important research priorities for emergency medicine and ranked their top 5 choices from a pre-specified list published by the ACEM researchers. Results were analysed using qualitative and quantitative research methods. Results: A total of 430 patients completed the survey, of which 218 were men (50.7%), with median age 44 years (interquartile range [IQR] 30–61 years, range 18–92 years). The top 5 priorities suggested by patients were cardiology, trauma, ED processes, mental health and haematology/oncology. The top 5 patient rankings of the ACEM researcher list were resuscitation, trauma, cardiology, infectious diseases and paediatrics. Older age groups tended to rank cardiology high, while trauma and resuscitation were ranked high among all age groups. There was moderate agreement between patients and ACEM researchers (? = 0.51, P = 0.03). Conclusions: The top 5 emergency medicine research priorities nominated by patients in ED were cardiology, trauma, ED processes, mental health and haematology/oncology, although many ‘system priorities’ were identified as well. These priorities were generally consistent with ACEM researchers, but patients also suggested alternative directions for future research.